(untitled) (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
Over the last 20 years, the Supplementary Health Market has seen a reduction in the number of Health Companies due to insolvency. There are several risks that can lead to this factor, and one of the main ones is the pricing risk. With this in mind, the present study sought to analyze the efficiency of different methods in calculating the pricing of supplementary health plans. To carry out the pricing, Monte Carlo simulation methods, Collective Risk Theory and Credibility Theory were used. The study found that the Credibility Theory showed the greatest efficiency for calculating the pricing of health plans, among the three methods analyzed, for the sample used.